Neonatal Asphyxia as a Risk Factor for Sensorineural Hearing Loss in Indonesian Children - Ratna Anggraeni; Wijana; Pudyastuti Rachyanti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Neonatal Asphyxia is one of the risk factors for hearing loss in children. Neonatal Asphyxiacauses cochlear damage due to lack of oxygenation and tissue perfusion which can lead to cell death.Objective: Determining the risk of Neonatal Asphyxia for the occurrence of sensorineural hearing lossin children. Methods: A case control study was done between July to September 2020. Children withsensorineural hearing loss are on study group and the control group is children with normal hearing.Participants were measured for previous labor history based on medical records that confirmed asphyxia.Participants were also examined for DPOAE and ABR / BERA. The measurement results were analyzedusing the Chi-Square test, which was significant if p <0.05. Results: Most participants aged 2-3 yearsexperienced hearing loss (65.96%) and normal (68.08%; p = 0.835). Participants of sensorineural hearingloss with Neonatal Asphyxia (57.4%) were more than non- Neonatal Asphyxia (42.6%; OR = 1.82; 95% CI0.81 - 4.13; p = 0.149). Conclusion: Neonatal Asphyxia increases the risk of sensorineural hearing loss by1.82 times compared to children without Neonatal Asphyxia.